The DREB transcription factor, a biomacromolecule, responds to abiotic stress by regulating the expression of stress-related genes - Zhang, Y.; Xia, P.
Abiotic stress is a crucial factor that affects plant survival and growth and even leads to plant death in severe cases. Transcription factors can enhance the ability of plants to fight against various stresses by controlling the expression of downstream genes. The dehydration response element binding protein (DREB)is the most extensive subfamily of AP2/ERF transcription factors involved in abiotic stress. However, insufficient research on the signal network of DREB transcription factors has limited plant growth and reproduction. Furthermore, field planting of DREB transcription factors and their roles under multiple stress also require extensive research. Previous reports on DREB transcription factors have focused on the regulation of DREB expression and its roles in plant abiotic stress. In recent years, there has been new progress in DREB transcription factors. Here, the structure and classification, evolution and regulation, role in abiotic stress, and application in crops of DREB transcription factors were reviewed. And this paper highlighted the evolution of DREB1/CBF, as well as the regulation of DREB transcription factors under the participation of plant hormone signals and the roles of subgroups in abiotic stress. In the future, it will lay a solid foundation for further study of DREB transcription factors and pave the way for the cultivation of resistant plants.
Keywords: ABIOTIC STRESS; CROPS; DREB TRANSCRIPTION FACTORS; PLANT HORMONES; SIGNAL PATHWAYS